2018
DOI: 10.3390/agronomy8050066
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Drought Stress by Nitrogen Application in Brassica campestris ssp. Chinensis L.

Abstract: Abstract:To assess the influence of drought stress on the growth and nitrogen nutrition status of pakchoi (Brassica campestris ssp. Chinensis L.) at different nitrogen (N) levels, the changes in N accumulation and enzyme activities involved in N assimilation were investigated. The drought was induced by adding polyethylene glycol (PEG) under hydroponic culture conditions. Pakchoi seedlings were exposed to a modified nutrient solution with different nitrogen concentration (N1, N2, and N3 represent 2, 9 and 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
(32 reference statements)
3
22
2
Order By: Relevance
“…Xiong et al therefore investigated the influence of drought stress and nitrogen supply on the growth of pak choi. Drought was simulated by adding polyethylene glycol under hydroponic culture conditions, resulting in a significant decline in plant water content, transpiration rate, shoot biomass, and shoot nitrogen concentration [18]. Their results further indicated that pak choi supplied with higher nitrogen concentration showed a significant better growth performance under drought stress compared to the controls.…”
Section: Abiotic Stress Responses and The Usage Of Rna-seq Methodologymentioning
confidence: 98%
“…Xiong et al therefore investigated the influence of drought stress and nitrogen supply on the growth of pak choi. Drought was simulated by adding polyethylene glycol under hydroponic culture conditions, resulting in a significant decline in plant water content, transpiration rate, shoot biomass, and shoot nitrogen concentration [18]. Their results further indicated that pak choi supplied with higher nitrogen concentration showed a significant better growth performance under drought stress compared to the controls.…”
Section: Abiotic Stress Responses and The Usage Of Rna-seq Methodologymentioning
confidence: 98%
“…Nitrogen is one of the most important and limiting factors for plant growth and productivity . Nitrogen fertilization significantly increased food, feed, and fiber production and thus reduced the pressure of global population growth .…”
Section: Nitrate‐n and Potential For Improving Nuementioning
confidence: 99%
“…Like water, nitrogen is very important for plant growth and productivity [17]. Generally, drought stress affects nitrogen uptake and transport to the aboveground plant parts because it decreases the transpiration rate and membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, drought stress affects nitrogen uptake and transport to the aboveground plant parts because it decreases the transpiration rate and membrane permeability. Another reason for the poor transport and metabolism of nitrogen is that both nitrate and ammonium need water for uptake and translocation to the aboveground plant parts for metabolism [17]. The regulation of nitrogen metabolism is very important for plant stress tolerance as most plant physiological processes are associated with it [18].…”
Section: Introductionmentioning
confidence: 99%